2021
DOI: 10.1371/journal.pone.0250633
|View full text |Cite
|
Sign up to set email alerts
|

Trends and predictors of in-hospital mortality among babies with hypoxic ischaemic encephalopathy at a tertiary hospital in Nigeria: A retrospective cohort study

Abstract: Background Globally, approximately 9 million neonates develop perinatal asphyxia annually of which about 1.2 million die. Majority of the morbidity and mortality occur in Low and middle-income countries. However, little is known about the current trend in incidence, and the factors affecting mortality from hypoxic ischaemic encephalopathy (HIE), in Nigeria. Objective We assessed the trends in incidence and fatality rates and evaluated the predictors of mortality among babies admitted with HIE over five years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 39 publications
1
4
1
Order By: Relevance
“…These findings confirm findings from previous studies [4,29]. However, unlike the findings of Ezenwa et al's study in Nigeria, outborn neonates did not appear to be at higher risk of neonatal death compared to their inborn counterparts [30]. This could be explained by the differences in referral pathways in Nigeria and Zimbabwe to their tertiary neonatal units, but further research into this field is required.…”
Section: Plos Global Public Health Neonatal Outcomes In Hospitalsupporting
confidence: 84%
“…These findings confirm findings from previous studies [4,29]. However, unlike the findings of Ezenwa et al's study in Nigeria, outborn neonates did not appear to be at higher risk of neonatal death compared to their inborn counterparts [30]. This could be explained by the differences in referral pathways in Nigeria and Zimbabwe to their tertiary neonatal units, but further research into this field is required.…”
Section: Plos Global Public Health Neonatal Outcomes In Hospitalsupporting
confidence: 84%
“…It is not possible to compare this with prevalence estimates per 1000 live births. These estimates are lower than a recent study in Nigeria (Ezenwa et al, 2021) reporting prevalence of 71 per 1000 admissions with 25.3% respectively where NE was defined in a term infant as the presence of encephalopathy or altered consciousness and multi-organ failure with a positive history of delayed cry at birth or required prolonged resuscitation at birth in addition to the presence of any of the neurological features as contained in the Sarnat and Sarnat classification.…”
Section: Discussioncontrasting
confidence: 55%
“…Suboptimal care is an important factor for encephalopathy and mortality. 39,40 A study in Nigeria found that the majority of neonates with asphyxia had poor quality care and had a delay in deciding to present at the appropriate health facility. 41 The findings from our study provide further evidence of an urgent need to implement root cause analysis of an adverse obstetric event at all three tiers of the health care system.…”
Section: Discussionmentioning
confidence: 99%